Pengaruh Disiplin Kerja dan LMX (Leader Member Exchange) terhadap Prestasi Kerja Karyawan dengan Motivasi Kerja Sebagai Variabel Intervening pada Bank Sultra Cabang Raha - Reni Inrawati; Nurwati Nurwati; Sri Maharani (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this study was to examine and explain the influence of work discipline and LMX on employee performance, mediated by work motivation, at Bank Sultra's Raha Branch. This study design was based on a quantitative approach with a cross-sectional survey data collection method. Data collection was conducted using a questionnaire instrument. The study sample consisted of all 53 employees at Bank Sultra's Raha Branch. Data analysis used Partial Least Squares (PLS) hypothesis testing. The results showed that work discipline had a positive and significant effect on employee work motivation and performance. Furthermore, LMX had a positive and significant effect on work motivation, but had an insignificant effect on employee performance. Work motivation was proven to have a positive and significant effect on employee performance. The results of this study also demonstrate that work motivation plays a partial mediator in the influence of work discipline on employee performance. This means that increased work motivation is significantly influenced by work discipline. Furthermore, work motivation has a significant contribution to improving employee performance. Furthermore, work motivation has been shown to act as a perfect mediator in the influence of LMX on employee performance. Therefore, it can be concluded that good work discipline and LMX can also make a real or significant contribution to improving employee performance, both directly and through the mediating role of work motivation.